Feminisms in social work research : promise and possibilities for justice-based knowledge - Wahab, Stephanie; Anderson-Nathe, Ben; Gringeri, Christina E. (London : Routledge, 2015)
'Social work as a profession and academic discipline has long centered women and issues of concern to women, such as reproductive rights, labor rights, equal rights, violence and poverty. In fact, the social work profession was started by and maintained in large part by women and has been home to several generations of feminists starting with recognized first wave feminists. This wide-ranging volume both maps the contemporary landscape of feminist social work research, and offers a deep engagement with critical and third wave feminisms in social work research. Showcasing the breadth and depth of exemplary social work feminist research, the editors argue that social work's unique focus on praxis, daily proximities to privilege and oppression, concern with social change and engagement with participatory forms of inquiry place social workers in a unique position to both learn from and contribute to broader social science and humanities discourse associated with feminist research. The authors attend here to their specific claims of feminisms, articulate deep engagement with theory, address the problematic use of binaries, and engage with issues associated with methods that are consistently of interest to feminist researchers, such as power and authority, ethics, reflexivity, praxis and difference. Comprehensive and containing an international selection of contributions, Feminisms in Social Work Research is an important reference for all social work researchers with an interest in critical perspectives'--
Includes bibliographical references and index.
Keywords: Social work with women; Feminism; Social service -- Research